Cancer and the breakdown of multicellularity: What Dictyostelium discoideum, a social amoeba, can teach us. (14th January 2021) - Mathavarajah, Sabateeshan; VanIderstine, Carter; Dellaire, Graham; Huber, Robert J.
Abstract: Ancient pathways promoting unicellularity and multicellularity are associated with cancer, the former being pro‐oncogenic and the latter acting to suppress oncogenesis. However, there are only a limited number of non‐vertebrate models for studying these pathways. Here, we review Dictyostelium discoideu m and describe how it can be used to understand these gene networks. D. discoideum has a unicellular and multicellular life cycle, making it possible to study orthologs of cancer‐associated genes in both phases. During development, differentiated amoebae form a fruiting body composed of a mass of spores that are supported atop a stalk. A portion of the cells sacrifice themselves to become non‐reproductive stalk cells. Cheating disrupts the principles of multicellularity, as cheater cells alter their cell fate to preferentially become spores. Importantly, D. discoideum has gene networks and several strategies for maintaining multicellularity. Therefore, D. discoideum can help us better understand how conserved genes and pathways involved in multicellularity also influence cancer development, potentially identifying new therapeutic avenues. Abstract : In cancer, malignant cells shift from promoting pathways of multicellularity towards those associated with unicellular functions. Cheating in Dictyostelium discoideum describes how cheaters skew differentiation to preferentially become spores. Cheating and oncogenesis both destabilize the principles of multicellularity. Thus, D. discoideum can be utilized to better understand the breakdown of multicellularity.